At home abroad: Transnational ageing in Silvia Baron Supervielle. Issue 3 (January 2017) - Averis, Kate
Abstract : This article explores the intersections of ageing, gender, and migration in the narrative prose works of Silvia Baron Supervielle. Born in Buenos Aires in 1934 and having lived in Paris and published in French for the best part of her life (since 1961), Baron Supervielle explores the challenges and freedoms posed by ageing as a 'cultural Other'. Through a focus on two key non-fictional narrative texts by the author, La Ligne et l'ombre ['The Line and the Shadow'] (1999) and Le Pays de l'écriture ['The Land of Writing'] (2002), with reference to more recent works, this article shifts the focus away from the processes of arrival and adaptation that dominate analyses of displacement to examine the evolution of transnational identity into late life in order to reveal a reconsideration of received ideas of both women's mobility and ageing in the works of this singular author.